Contrast-enhanced ultrasound (CEUS) in assessing early response among patients with invasive breast cancer undergoing neoadjuvant chemotherapy. (April 2017) - Saracco, Ariel; Szabó, Botond K; Tánczos, Ervin; Bergh, Jonas; Hatschek, Thomas
Background: One of the big challenges in onco-radiology is to find a reliable imaging method that may predict early response during the first cycles of any neoadjuvant chemotherapy. Purpose: To evaluate the use of real-time harmonic contrast-enhanced ultrasound (CEUS) in predicting early response in breast cancer tumors under neoadjuvant chemotherapy (NAC) treatment. Material and Methods: Nineteen consecutive patients with invasive breast cancer were evaluated with a bolus dose of 2.4 mL contrast agent using CEUS, before and after two cycles of epirubicin and docetaxel. The lognormal function was used for quantitative analysis of kinetic data to evaluate early response. Results: There was statistically significant difference in time-to-peak ( tp ) between responders and non-responders (two sample t-test, P = 0.027) where tp was significantly longer at the week 5 than at the baseline scan among responders when compared to non-responders. Conclusion: In-flow of intravascular contrast agent in tumors is significantly slower in responders at real-time harmonic CEUS, and might be effectively used for the evaluation of early response to chemotherapy in invasive breast cancer. However, further investigations in a larger and more heterogeneous population should be performed to corroborate the reliability of the method.